Comparative Analysis Of Human Resource Management Practices In Indonesia And The Uk: A Review Of Interculturalism In Context Of Global Organizations - Mochamad Freski Dino Fava; Bayu Rizqi Putra Mahendra Tratuhany; Firmansyah Nurzam Ferriyadi; Reza Dinda Agustin; Nessa Aulia Jalapuspa (International Journal of Social, Economic, and Business, 2024)
This research aims to compare human resource management (HRM) practices in Indonesia and the UK in the context of interculturalism in global organizations. The research method used is a literature study with a descriptive-qualitative approach, which describes cross-cultural HRM practices in both countries. Data was collected through literature study from various sources such as journal articles, conferences, websites and related documents. The results of a comparative analysis of HRM practices show significant differences in recruitment, occupational safety and health, selection, performance appraisal, training, and compensation systems between the two countries. The implication of this research is to provide in-depth insight into the dynamics of interculturalism in the context of global organizations in HR management, as well as providing a basis for developing a more effective approach in managing cross-cultural workforces in the current global context. In addition, this research also highlights the importance of leadership support, changes in employee mindsets, rewards, training, flexibility, and implementation of intrapreneurship in the context of HRM practices in both countries.